Optimization of hydro-system management and operation - abstract - Yen, William W-G, author; Colorado State University, publisher (Colorado State University. Libraries, 2014)
Abstract of award lecture "Optimization of hydro-system management and operation" given on March 25, 2014, by William W-G Yeh, winner of the 2014 Hydrology Days Award.
Hydrology days 2014
AGU hydrology days 2014
2014 annual AGU hydrology days was held at Colorado State University on March 24 - March 26, 2014.
Keywords: Hydrology -- Congresses; Award winners